Hubungan Pendidikan dan Penghasilan Dengan Perilaku Hidup Bersih dan Sehat - S., Tatang Roni; Ruhmawati, Tati; Sukandar, Denny (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2013)
Background:The rapid development in the globalization were demographicand epidemiological transition, behavioral and lifestyle-based disease problems associated with behavioral and social culture tends to be more complex. The purpose of this research was to know the relationship betweenincome and education with the clean and healthy behavior. Methods:It was an observational reseach using cross-sectional design. The study population was 60 households muslim community who have children resident inSub District Sukamiskin village sub district ofArcamanik Bandung, while the sample is mostly housewives drawn from the population of 36 people with simple random sampling technique. The collected data was processed and analyzed for univariate, bivariate using Pearson Product Moment test and multivariate analysis using the path (path analysis). Results: There were 47.2% of respondents who had formal education at intermediate level, 25% had non-formal education (courses), 47.2% of them had finished 12 year of study.And 22.2% had non-formal education for at least one year. The respondents who had income more than 1 million/month was 30.6%, and 33.3% of them hadÂ 0.5 million additional income. Generally, they had good personal hygiene (hand washing, get a bath of 91.7% and 52,8% respectively). The respondent had a habit on opening the window of 44.4% and 77.8% had covered water container. Conclusion: Based on statistical analysis known that education ang income tend to have association significantly with clean and healthy behavior (p-value < 0,05). Keywords:Education and income, Clean and healthy behavior.